Capitalist tendencies in Jeremiah 6:13-20 and the church in economically unstable Nigeria - UROKO, FAVOUR (Jurnal Koinonia: Fakultas Filsafat Universitas Advent Indonesia, 2024)
This article examines the capitalist tendencies in Jeremiah 6:13–20 and their implications for Nigeria. Jeremiah 6:13–20, in particular, presents a striking critique of the pervasive greed and corruption among the leaders and people of Judah. This passage reveals the prophet Jeremiah's denunciation of materialistic pursuits and unethical practices that prioritise wealth accumulation over justice and righteousness. In Nigeria, the prophets and priests are giving prophecies for self-gain. They prophesy to the people about the number of enemies chasing them or stopping their progress in their bid to get money from the people. Families have been disintegrated because of some of these prophecies. It was on this premise that Jeremiah noted that these prophets practice deceit. This is a qualitative study using the narrative method. The data was from secondary literature. The data was analysed using content analysis. Emerged themes include: a) unrestrained greed and materialism; b) corruption and deception; c) neglect of justice; d) false security in wealth; and d) consequences of unchecked capitalism. Recommendations are discussed.